Hukum Jual Beli Sepeda Motor Hasil Penarikan Debt Colector Leasing Dari Konsumen Yang Gagal Bayar Perspektif Yusuf Qhardawi Studi Kasus Desa Tanjung Gunung Kecamatan Buntu Pane - Paristiwa, Arif; Harahap, Abd Rahman (IAI Darussalam, 2024)
This research discusses the legal status of buying and selling motorbikes resulting from the withdrawal of leasing collectors from consumers who failed to pay from the perspective of Yusuf al-Qardawi, a case study of Tanjung Gunung Village, Buntu Pane District, even though it is equally known that the basis of buying and selling is as an effort by the human being to maintain and meet their living needs. Furthermore, Islam does not limit a person's desire to seek wealth, as long as it is carried out according to the general principles that apply, namely halal and good by means of mutual cooperation and helping each other. Based on these problems, further research was carried out regarding the practice and law of buying and selling motorbikes resulting from leasing collectors from consumers who failed to pay, Yusuf Qardawi. The writing of this thesis uses qualitative methods, namely in the form of field research. This research is also descriptive analytical in nature, namely the author systematically describes the object being researched and then analyzed. So we can conclude the law based on the perspective of Yusuf Qardhawi's opinion that buying and selling motorbikes resulting from the withdrawal of the leasing collector from consumers who fail to pay is prohibited (haram). The main trading point of buying and selling motorbikes resulting from the withdrawal of the leasing collector will result in mutual assistance between the seller and the buyer in terms of elements of disobedience and injustice, namely committing fraud.